2016
DOI: 10.3389/fmicb.2016.01257
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Genetic Basis of the Resveratrol Biosynthesis Pathway in an Endophytic Fungus (Alternaria sp. MG1) Isolated from Vitis vinifera

Abstract: Alternaria sp. MG1, an endophytic fungus previously isolated from Merlot grape, produces resveratrol from glucose, showing similar metabolic flux to the phenylpropanoid biosynthesis pathway, currently found solely in plants. In order to identify the resveratrol biosynthesis pathway in this strain at the gene level, de novo transcriptome sequencing was conducted using Illumina paired-end sequencing. A total of 22,954,434 high-quality reads were assembled into contigs and 18,570 unigenes were identified. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The N50 length of the unigenes was 2,451 bp, which was longer than the N50 obtained from the transcriptome sequencing of Alternaria sp. MG1 (N50 = 2,153 bp) using the Illumina HiSeq 2500 platform in a previous study (Che et al, 2016). Collectively, the results indicate that the quality and integrity of the obtained sequences are high.…”
Section: Discussionmentioning
confidence: 99%
“…The N50 length of the unigenes was 2,451 bp, which was longer than the N50 obtained from the transcriptome sequencing of Alternaria sp. MG1 (N50 = 2,153 bp) using the Illumina HiSeq 2500 platform in a previous study (Che et al, 2016). Collectively, the results indicate that the quality and integrity of the obtained sequences are high.…”
Section: Discussionmentioning
confidence: 99%
“…from a mangrove plant Myoporum bontioides; Wang et al 2014b), emtomopathogenic bacteria (Photorhabdus luminescens, Eleftherianos et al 2007; Bacillus sp., Kumar et al 2012), several edible mushrooms (Peng et al 2015), sponge (Antarctic sponge Kirkpatrickia variolosa, Jayatilake and Baker 1995), and moth larva (dried silkworm larva of Bombyx mori, Kikuchi et al 2004). A recent transcriptome analysis provided the evidence at the gene level that stilbenes in the endophytic fungus Alternaria could be synthesized by CHS (Che et al 2016), and a recent structural analysis revealed that the stilbene 2-isoprpyl-5-[(E)-2-phenylvinyl] benzene-1,3-diol in bacteria Photorhabdus is synthesized by the collaboration of two enzymes, the unusual b-ketosynthase StlD and the aromatase StlC (Mori et al 2016).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…The draft model was obtained via homologous alignment with reference strains using previously described procedures, followed by manual curation. Firstly, 97 reactions in the biosynthesis pathways of phenylpropanoid, stilbene synthesis, flavonoid synthesis, and lignin biosynthesis were added to the model by referring to the KEGG database, BLASTp, and literature reports [24, 37]. A total of 220 transport reactions annotated from the TCDB database and 133 exchange reactions were also added into the model i YL1539.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleic acids (DNA and RNA), proteins, lipids, carbohydrates, and ash were considered in the biomass equation. Total DNA and RNA were extracted [37] and their specific composition was calculated based on the genome sequence with a GC content of 50.96%. Amino acid composition was analyzed using an amino acid analyzer (L-8900, HITACHI, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation